1969
DOI: 10.1063/1.1664797
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation Method for a Nonlinear Wave Modulation. II

Abstract: A perturbation method given in a previous paper of this series is applied to two physical examples, the electron plasma wave and a nonlinear Klein-Gordon equation. In these systems, and probably in most physical systems, an assumed condition for a mode of l = 0 is not valid. Consequently, the direct application of the method is impossible. In the present paper, we shall illustrate by these examples how this difficulty can be overcome to allow us to use the method. As a result we shall find that, in either case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(86 citation statements)
references
References 2 publications
2
84
0
Order By: Relevance
“…We have shown that the slow variation of the wave's amplitude in space and time may be modeled via the longestablished multiple scale ("reductive perturbation") method Asano et al, 1969). One thus obtains explicit conditions for the occurrence of "modulational instability", which is related to wave collapse, or may possibly result in the formation of "localized envelope structures".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that the slow variation of the wave's amplitude in space and time may be modeled via the longestablished multiple scale ("reductive perturbation") method Asano et al, 1969). One thus obtains explicit conditions for the occurrence of "modulational instability", which is related to wave collapse, or may possibly result in the formation of "localized envelope structures".…”
Section: Discussionmentioning
confidence: 99%
“…What follows is essentially an implementation of the long known "reductive perturbation" technique Asano et al, 1969;Shimizu and Ichikawa, 1972;Kako, 1974;Kakutani, 1974), which was first applied in the study of electron plasma Asano et al, 1969) and electron-cyclotron (Hasegawa 1970(Hasegawa , 1972 waves, more than three decades ago.…”
Section: Weakly Nonlinear Oscillation Regimementioning
confidence: 99%
“…We employ a multiple-scale perturbation technique [62,63] to derive the evolution equation of a slowly varying weakly nonlinear wave amplitude of IAW packets in a q nonextensive plasma. Here, we consider A as the state vector {A}(= n i , u i , φ), describing the system's state at a given position x and time t. Small deviations will be considered from the equilibrium state…”
Section: Derivation Of Nls Equation: Pertubative Approachmentioning
confidence: 99%
“…The standard method for studying this mechanism is a multiple space and time scale technique [6,7], which leads to a nonlinear Schrödinger-type equation (NLSE) describing the evolution of the wave envelope. It has been shown that, under certain conditions, waves may develop a Benjamin-Feir-type (modulational) instability (MI), i.e.…”
Section: Introductionmentioning
confidence: 99%